Lateral Dye‐Sensitized Microscale Solar Cells via Femtosecond Laser Patterning. Issue 6 (3rd August 2016) - Zhang, Xi; Huang, Yinggang; Bian, Hao; Liu, Hewei; Huang, Xuezhen; Jiang, Hongrui
Abstract : Lateral photoelectrode‐counter electrode structure with microscale interdigital fingers of TiO2 /FTO film is constructed for dye‐sensitized solar cells by femtosecond laser patterning. A highest photon‐to‐electron efficiency of 5.18% under AM 1.5G is achieved. A novel tandem DSSC is fabricated with ultracompact structure due to this lateral design, accomplishing 6.21% photon‐to‐electron efficiency.